AvrRpm1 Functions as an ADP-Ribosyl Transferase to Modify NOI Domain-Containing Proteins, Including Arabidopsis and Soybean RPM1-Interacting Protein4. Issue 11 (23rd September 2019) - Redditt, Thomas J.; Chung, Eui-Hwan; Karimi, Hana Zand; Rodibaugh, Natalie; Zhang, Yixiang; Trinidad, Jonathan C.; Kim, Jin Hee; Zhou, Qian; Shen, Mingzhe; Dangl, Jeffery L.; Mackey, David; Innes, Roger W.
Abstract : The Pseudomonas syringae effector protein AvrRpm1 ADP ribosylates RIN4 proteins from Arabidopsis and soybean, which promotes association of RIN4 with EXO70E2 and suppression of callose deposition. Abstract: The Pseudomonas syringae effector protein AvrRpm1 activates the Arabidopsis ( Arabidopsis thaliana ) intracellular innate immune receptor protein RESISTANCE TO PSEUDOMONAS MACULICOLA1 (RPM1) via modification of a second Arabidopsis protein, RPM1-INTERACTING PROTEIN4 ( At RIN4). Prior work has shown that AvrRpm1 induces phosphorylation of At RIN4, but homology modeling indicated that AvrRpm1 may be an ADP-ribosyl transferase. Here, we show that AvrRpm1 induces ADP-ribosylation of RIN4 proteins from both Arabidopsis and soybean ( Glycine max ) within two highly conserved nitrate-induced (NOI) domains. It also ADP ribosylates at least 10 additional Arabidopsis NOI domain-containing proteins. The ADP-ribosylation activity of AvrRpm1 is required for subsequent phosphorylation on Thr-166 of At RIN4, an event that is necessary and sufficient for RPM1 activation. We also show that the C-terminal NOI domain of AtRIN4 interacts with the exocyst subunits EXO70B1, EXO70E1, EXO70E2, and EXO70F1. Mutation of either EXO70B1 or EXO70E2 inhibited secretion of callose induced by the bacterial flagellin-derived peptide flg22. Substitution of RIN4 Thr-166 with Asp enhanced the association of At RIN4 with EXO70E2, which we posit inhibits its callose deposition function. Collectively, these data indicate that AvrRpm1 ADP-ribosyl transferase activity contributes to virulence by promoting phosphorylation of RIN4 Thr-166, which inhibits the secretion of defense compounds by promoting the inhibitory association of RIN4 with EXO70 proteins.